PERAN GURU DALAM MEMBENTUK KARAKTER SISWA DI ERA MODERNISASI - Farid Haluti; Nimim Ali; Jumahir Jumahir; Suma K Saleh; Ni'mah Wahyuni (JURNAL PENDIDIKAN GLASSER, 2023)
The modernization era is an era where there is a change from traditional to advanced (modern) as it is today which can be seen from various aspects including education. In the era of modernization, the educational aspect focuses on character education. This is because character education has the aim of shaping the character of students to become good individuals and be able to keep up with the times, and it can be formed by the role of teachers. This study aims to be able to know and describe the role of teachers in shaping student character in the modernization era. The research method is carried out qualitatively, namely with a literature study approach (literature study). The results of this study show that the role of teachers in the field of education in an effort to shape the character of students in the modernization era as it is today is very important in order to realize the purpose of character education. From the results of the study, it can be concluded that shaping the character of students, is carried out with the efforts of the teacher so that they can shape the character of students into good individuals and are able to keep up with the times.